2019
DOI: 10.4114/intartif.vol22iss63pp162-195
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Adaptive Computational Intelligence-based Multisensor Data Fusion applied to real-time UAV autonomous navigation

Abstract: Nowadays, there is a remarkable world trend in employing UAVs and drones for diverse applications. The main reasons are that they may cost fractions of manned aircraft and avoid the exposure of human lives to risks. Nevertheless, they depend on positioning systems that may be vulnerable. Therefore, it is necessary to ensure that these systems are as accurate as possible, aiming to improve navigation. In pursuit of this end, conventional Data Fusion techniques can be employed. However, its computational cost ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 62 publications
(91 reference statements)
0
8
0
Order By: Relevance
“…1 ). The ratio of 8:2 is commonly used as a rule-of- thumb when splitting a dataset into training and test sets; a recent machine-learning study also reported that using 70% or 80% of the data as a training set showed the best result [ 15 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…1 ). The ratio of 8:2 is commonly used as a rule-of- thumb when splitting a dataset into training and test sets; a recent machine-learning study also reported that using 70% or 80% of the data as a training set showed the best result [ 15 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…1 ). The ratio of 7:3 is commonly used as a rule-of-thumb when splitting a dataset into training and test sets; a recent machine-learning study also reported that using 70% or 80% of the data as a training set showed the best result [ 17 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…In the literature, there is a study that investigated the influence of the number of training periods on this data set. The study points out the methodology applied in the investigation was not an MLP but an approach using a Fuzzy system [26].…”
Section: Cross-validation Training -Hold Outmentioning
confidence: 99%